Pearl millet milling : comparison between traditional Namibian fermentation - semi-wet milling and dry milling - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2009.